INTEGRATING BEHAVIORAL ECONOMICS INTO MONETARY POLICY DECISION-MAKING: A THEORETICAL REVIEW - Khampheng Vongchanh (Count : Journal of Accounting, Business and Management, 2025)
This study aims to explore how behavioral economics can be systematically integrated into monetary policy decision-making frameworks to enhance their theoretical realism and practical effectiveness. Traditional monetary models, grounded in rational expectations, often fail to anticipate how cognitive biases distort public responses to interest rates, inflation targeting, and central bank communication. Using a structured literature review method, the research analyzes peer-reviewed publications, institutional reports, and theoretical models from 2015 to 2025. The findings reveal that behavioral biases such as present bias, loss aversion, overconfidence, and framing effects significantly influence the transmission and credibility of monetary policy. However, most central banks still rely on models that treat these behavioral patterns as peripheral, leading to inefficiencies in policy design and communication. The novelty of this study lies in the development of a conceptual framework and a behavioral taxonomy tailored for monetary policy applications—bridging gaps between behavioral theory and macroeconomic practice. Additionally, it highlights the institutional inertia and narrative misalignment that often obstruct the operationalization of behavioral insights in central banking. The study proposes that adaptive learning models and narrative-sensitive strategies offer promising pathways for reforming monetary frameworks. In conclusion, integrating behavioral economics is not just a theoretical enhancement but a necessary evolution for more credible, inclusive, and psychologically grounded monetary policy. This research contributes to both academic discourse and global policymaking by offering a unified approach to behavioral monetary theory.